Racial Socialization in White Parent-child Dyads: An Observational Approach. - Zucker, Jenna K.; Patterson, Meagan (Journal of Child & Family Studies, 2025)
This paper explores White parents' racial socialization behaviors, both as reported in interviews and as observed in a laboratory interaction in which White parent-child dyads (N = 10, children aged 10–12) were presented with two race-relevant news clips and asked to discuss the clips. Results indicate that although parents expressed an interest and sense of comfort surrounding race-related conversations with their children when interviewed, parents employed a combination of colorblind and color-conscious messages when discussing race-related current events with their children during the observation session. Other related themes also emerged in interviews and observed parent-child conversations about race, such as the role of the media, valuing of diversity, and race as a contemporary versus historical issue. Highlights: Current research on racial socialization in White families largely relies on self-report data and/or retrospective reports of older adolescent children. Our study combines observations of parent-child conversations and parent interviews to explore the racial socialization strategies used. Parents in our sample used a combination of colormute and color-conscious strategies when discussing race with their children.